Aerobic bacteria study, clinical spectrum, and outcome of patients with community-acquired multidrug-resistant pathogens - Chandra Sekhar Talari Sree; Ravi Shankar Calerappa; Geethanjali Anke (Journal of Family Medicine and Primary Care)
Context: Infectious diseases are the leading cause of death in developing countries like India. Hence, even small relative increases in the mortality rate for infections due to multidrug-resistant pathogens would lead to substantial increases in the number of deaths as a result of infections worldwide. Aims: The aim of the study was to study the microbiological data of community-acquired pathogens and the corresponding outcomes due to antibiotic-resistant versus antibiotic-susceptible bacterial microorganisms. Settings and Design: A single-center prospective cohort study for two years undertaken during the study period of March 2022 to 31 October 2023. Materials and Methods: All clinical samples of 402 patients diagnosed microbiologically as community-acquired infections were included. Culture samples were collected and processed according to standard operating procedures and clinical details were recorded. Statistical Analysis Used: Categorical variables were expressed as counts and percentages. Fisher’s exact test was used for testing differences in proportions. Two-sided distribution P values of <0.05 were considered significant. Results: Among Gram-positive organisms, Staphylococcus aureus and Streptococcus pyogenes were predominant isolates. Escherichia coli and Klebsiella species were the majority of the pathogens among Gram-negative isolates. Mortality rates observed in community-acquired respiratory tract infections (CA-RTIs), community-acquired urinary tract infections (CA-UTIs), community-acquired skin and soft tissue infections (CA-SSTIs), and community-acquired bloodstream infections (CA-BSIs) were 13.6%, 6.56%, 4.5%, and 31.5%, respectively. The length of hospital stay of more than three days was found as 56.06%, 36.2%, 40.9%, and 73.6% in CA-RTIs, CA-UTIs, CA-SSTIs, and CA-BSIs, respectively. Conclusions: Performing cultures earlier during hospitalization and determining the timing of colonization can allow more targeted choices and reduce morbidity and mortality rates among infected patients.